CONSUMER ACCEPTANCE ON COOKIES OF TARO FLOUR FORTIFIED WITH FISH PROTEIN CONCENTRATE FROM TILAPIA (Oreochromis niloticus) - Paridah Hasibuan; Dewita Dewita; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the level of consumer acceptance on cookies of taro flour fortified with tilapia protein concentrate and to determine the best concentration of cookies of taro flour fortified with fish protein concentrate (FPC) from tilapia (Oreochromis niloticus). The method used in the research wasexperimentalwith a non-factorial Completely Randomized Design (CRD) consisting of 4 levels of treatment, namely the addition of  tilapia protein concentrate of 0% (K0), 5% (K1), 10% (K2), and 15% (K3). The observed parameters were proximate analysis (moisture, ash, fat, protein, carbohydrate) and organoleptic (color, aroma, flavor,and texture). The results showed that the K3 treatment was the best treatmentwith the characteristics of light brown,  odorless fish, less sweet and fish flavor, dense and crispy. Furthermore, the proximate value wasmoisture of 3,93%, ash content of 1,84%, fat content of 0,21%, protein content of 19,21%, and carbohydrate content of 72,11%. Keywords: cookies, fish protein concentrate (FPC), fortification.